(untitled) (Historia, 2021)
Although the judiciary forms a critical branch in the process of governance as an independent arbitrator, it remains in many ways an inaccessible system for ordinary citizens, with its legalistic jargon and endlessly complicated processes. Public interest in legal processes continues to flourish, however, with recent high profile court cases such as the Oscar Pistorius trial and the technological developments such as social media combining to make headlines on a scale never seen before. In recent years, a growing number of publications do, however, capture the complex processes of the judiciary in a more consumer friendly manner, yet without the poor aftertaste of sensationalism. Under Devil’s Peak falls squarely into this position.